Gastric volvulus in children: Experience of 6 years at a tertiary care centre - Pradeep S; Agrawal Amit; Mishra Pankaj; Sanghvi Beejal; Parelkar Sandesh; Joshi Milind (Wolters Kluwer Medknow Publications, 2010)
Background: The aim of the study was to review the cases of all children who had gastric volvulus from 2002 to 2007 at a tertiary care centre in India and to compare the outcome of management with the reported series on gastric volvulus in a paediatric age group. Materials and Methods: This was a retrospective study of eight children with an age range between 10 days and 2 years who were managed for gastric volvulus between 2002 and 2007. The records of these patients were reviewed for clinical features, investigations, management and outcome. Results: All patients were less than 3 years of age with female preponderance (n = 5). Three patients had acute presentation and three had acute-on-chronic symptoms, while two had chronic gastric volvulus. The commonest symptom was abdominal distension. Two patients were diagnosed by barium studies and six had clinical suspicion because of their symptoms and were confirmed intra-operatively. Seven had secondary gastric volvulus of organo axial type with associated pathologies as congenital diaphragmatic hernia (n = 5), Para oesophageal hiatus hernia (n = 2), and one had primary gastric volvulus in a postoperative period in an operated case for a tracheo-oesophageal fistula (n = 1). Seven patients were symptom free at follow-up; one patient succumbed due to septicaemia in the immediate post-operative period which was not related to the pathology of gastric volvulus. Conclusion: Gastric volvulus is a rare condition in children and requires prompt diagnosis and urgent intervention in acute presentation where it mimics acute abdomen and strong clinical suspicion.